Realidade aumentada como apoio à aprendizagem de vetores na educação superior - Pires, Glice Rocha (2022)
Higher education students have been facing challenges in learning Analytic Geometry, the sub-area of Mathematics that links Algebra and Geometry fields. Within Analytic Geometry, the study of Vectors is introduced as an algebraic resource that serves as an instrument for solving geometric problems and vice versa. The study of Vector Algebra has strong applicability in several fields of knowledge, such as Physics, Engineering, Computing, Economics, etc. Therefore, the student must be well trained in this regard. Nevertheless, the learning difficulties related to basic Vectors concepts and operations are evident. Disciplines that address this issue in higher education require a high level of abstraction from the student and usually adopt teaching materials that are poorly contextualized, disfavoring learning approaches that make sense to the student and take into account their educational needs. Many current technologies assist learners in problematic educational contexts, such as augmented reality. In this context, this research aimed to develop an augmented reality solution to make the teaching and learning process of Vectors more meaningful, with a visual and contextualized mathematical approach. For this, the research went through methodological procedures based on Design Thinking, once it is an approach that seeks an innovative solution centered on the needs of end-users. The target audience of the research was composed of undergraduate students from the Federal University of Rio Grande do Norte (UFRN) who were taking the Vectors and Analytical Geometry (VAG) course. The research was able to develop a prototype of an augmented reality mobile application that stimulates the learning of vector concepts and operations. The research product was evaluated in two ways. First, it was analyzed whether the application had resources for addressing needs identified during the initial stages of the research. Following that, the application was tested in VAG classes in the remote teaching model, due to restrictions imposed by UFRN related to the covid-19 pandemic. With experimentation, it was possible to evaluate the educational potential of the application, by analyzing the impacts of the application on the students' learning experience. The research made possible several findings about the educational tool produced: it is suitable for mathematics teaching; it enables a visual teaching approach of Vectors and it promotes visualization and understanding of vector concepts, operations and real-life applications. With game elements, it deals with vector concepts interactively and dynamically, within a context that makes sense to the student. It is expected that the present work can foster new research on the same theme and that the developed solution is taken forward in favor of a more enriching learning experience.